PENGARUH DISCOVERY LEARNING DAN MOTIVASI TERHADAP SIKAP KRITIS MAHASISWA PADA MATERI LARUTAN - Aswana aswana (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
Learning chemistry in solutions of material requires a very high kreaktifitas can improve students critical stance to state opinions in determining the concentration of the substance.For that lecturer required creative in the selection and application of strategy, method, model or approach.This research aims to know the influence of learning model of Discovery Learning and motivation towards the critical attitude of college students on the material of the solution in the Faculty of Agriculture University of Muara Bungo lesson 2017/2018 year. The research is the research experiments against the 2 samples, and every class is the class totaled 30 students with each given different treatment.Research data obtained from the now late for second class sample.Now the end result is analyzed by using normaliatas, its homogeneity test and analysis of varian (ANAVA) one lanes. Research results show that F > F count table i.e. 8,23> 4,18, Concluded that there are perngaruh motivation and critical attitude of students taught a method of discovery learning.